PROBLEM OF MALARIA INFECTION - ., Soebaktiningsih (Universitas Muhammadiyah Malang, 2011)
Malaria is still Public Health Problem in tropical country. Failure of Mefloquine ? Artesunate combination treatment of uncomplicated Plasmodium falciparum beginning to fail is due to the delayed clearance times and elevated Artesunate IC50, suggest thatArtesunate resistance may be emerging on background of Mefloquine resistance ( Rogers et al 2009). Pathogenesis of malaria in pregnancy is related to the ability of Plasmodium falciparum intra erythrocyte to sequester in the placenta. Study to understand the molecular basis of susceptibility to malaria in pregnancy has been advanced through the discovery of Chondroitin Sulfat A (CSA) molecule that support the accumulation of infected erythrocytes (IE) by Plasmodium falciparum in the placenta